Water pollution : assessment and management - Kumar, Arvind, 1953-; Tripathi, G. (Delhi : Daya Pub. House, 2004)
Contributed articles; with reference to India.
Includes statistical tables.
Keywords: Water -- Pollution -- India; Water conservation -- India; Water quality management -- India